Translocation and Aquaculture Impact on Genetic Diversity and Composition of Wild Self-Sustainable Ostrea edulis Populations in the Adriatic Sea - Šegvić-Bubić, Tanja; Žužul, Iva; Talijančić, Igor; Ugrin, Nika; Lepen Pleić, Ivana; Žuvić, Luka; Stagličić, Nika; Grubišić, Leon (Frontiers in Marine Science, 2020)
The European flat oyster, Ostrea edulis, is a keystone species suffering major population declines due to overfishing, habitat loss and parasite diseases. Knowledge of its fine-scale population genetic structure and connectivity, needed for effective conservation, restoration and management, is largely lacking. Along the eastern Adriatic Sea, genotyping of 1178 O. edulis individuals at 12 microsatellite loci was conducted, grouping the sampled populations by geographical origin (North, Middle, South Adriatic), shell-farm association (farmed, farm-impacted, wild oysters) and sampling year (2017, 2018), in order to explore spatio-temporal genetic variation and potential footprint of known human-mediated spat translocation events for aquaculture purpose. Short-term temporal genetic structuring of O. edulis populations was less pronounced compared to their spatial variability, which showed genetic discontinuity between O. edulis populations from different geographical regions, with the main boundary separating the North from the Middle and South Adriatic, and the weaker one limiting the flow between the Middle and South Adriatic. While the present culture practise and ongoing spat translocation promotes genetic heterogeneity in the investigated farms, reduced genetic diversity and smallest effective populations size of impacted, i.e. farm-associated O. edulis was consistently recorded in all geographical regions. Taken together, the results reflect regional oceanographic features, ongoing spat translocation and intensive harvesting, which might have reduced the wild O. edulis densities below the critical threshold for reproductive success, compromising settlement and favoring unidirectional gene-flow towards higher density farmed O. edulis. Genetic structure of Adriatic O. edulis populations revealed some concerning demographic changes and farm-wild oyster interactions and hence further investigation and management recommendations are given.